Cervical Carcinoma Metastasizing to the Orbit: A Case Report - Yousefnezhad, Azadeh; Reyhaneh Yousefi Sharami, Seyedeh (International Journal of Psychosocial Rehabilitation, 2020)
Metastasis to the orbit is a rare and unusual complication of cervical cancer. The most common organs for cervical cancer metastasis are the lungs and the liver. Only a handful of reports exist in the literature about cervical adenocarcinoma metastasizing to structures of the eyes. We report a case of a 52-year-old woman with a history of cervical adenosquamous carcinoma presenting with symptoms of headache and eye pain, which eventually revealed metastasis to the orbit with lympho-vascular involvement. While rare, development of ocular symptoms in patients suffering from cervical malignancies should alert physicians to possible ocular tumor invasion, a condition that is generally perceived to harbor a poor prognosis.